Comparative analysis of machine learning techniques in optimal site selection - Aurnab, Aukik; Choudhury, Shaktiman; Ruhan, Shoubhick Roy; Rifaiya Abrar, Shikh Muhammad; Hossain Rabbi, S.M. Riyadh (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.